A framework for developing an ergonomic programme to reduce MSD in the workplace. (12th May 2011) - Sylla, Cheickna; Samra, Yassir M.; Boon-long, Nitipong
Musculoskeletal disorders (MSD) are one of the main causes of health and safety problems in the workplace and have resulted in millions of dollars in additional health related expenses to companies and organisations. For a number of years, the Occupational Safety and Health Administration (OSHA) proposed an ergonomics programme standard in order to reduce and eventually eliminate such problems. Yet, companies are skeptical about such a standard and do not want to invest in the proposed ergonomics programme. A cost/benefit justification framework to build managers' awareness of the full benefits that can be gained from such ergonomics programme is needed. This paper proposes such framework for justifying ergonomics investments which could be developed for targeting MSD problems. Data were collected from various sources including Bureau of Labor Statistics, Healthcare Utilisation Project, and OSHA's proposed Ergonomics Standard Program. Results from the simulated application of the proposed framework showed that the value of ergonomics project could significantly increase the original project value.